The energy sensor OsSnRK1a confers broad-spectrum disease resistance in rice - Filipe, Osvaldo; De Vleesschauwer, David; Haeck, Ashley; Demeestere, Kristof; Höfte, Monica (Scientific reports, 2018)
Sucrose non-fermenting-1-related protein kinase-1 (SnRK1) belongs to a family of evolutionary conserved kinases with orthologs in all eukaryotes, ranging from yeasts (SnF1) to mammals (AMP-Activated kinase). These kinases sense energy deficits caused by nutrient limitation or stress and coordinate the required adaptations to maintain energy homeostasis and survival. In plants, SnRK1 is a global regulator of plant metabolism and is also involved in abiotic stress responses. Its role in the response to biotic stress, however, is only starting to be uncovered. Here we studied the effect of altered SnRK1a expression on growth and plant defense in rice. OsSnRK1a overexpression interfered with normal growth and development and increased resistance against both (hemi)biotrophic and necrotrophic pathogens, while OsSnRK1a silencing in RNAi lines increased susceptibility. OsSnRK1a overexpression positively affected the salicylic acid pathway and boosted the jasmonate-mediated defense response after inoculation with the blast fungus Pyricularia oryzae . Together these findings strongly suggest OsSnRK1a to be involved in plant basal immunity and favor a model whereby OsSnRK1a acts as a master switch that regulates growth-immunity trade-offs.